2013
DOI: 10.1063/1.4806998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure, temperature, and hydrogen during graphene growth on SiC(0001) using propane-hydrogen chemical vapor deposition

Abstract: Graphene growth from a propane flow in a hydrogen environment (propane-hydrogen chemical vapor deposition (CVD)) on SiC differentiates from other growth methods in that it offers the possibility to obtain various graphene structures on the Si-face depending on growth conditions. The different structures include the (6√3 × 6√3)-R30° reconstruction of the graphene/SiC interface, which is commonly observed on the Si-face, but also the rotational disorder which is generally observed on the C-face. In this work, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…[24,25] Depending on the growth conditions, either the samples are hole-doped and the graphene lies on a hydrogen-passivated SiC surface, or they are n-doped and the graphene lies on a carbon-rich buffer layer. [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…[24,25] Depending on the growth conditions, either the samples are hole-doped and the graphene lies on a hydrogen-passivated SiC surface, or they are n-doped and the graphene lies on a carbon-rich buffer layer. [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…However, to date, high quality Gr growth has been demonstrated only on a few semiconducting or semi-insulating materials, such as silicon-carbide [38][39][40]111,112] and, more recently, germanium [113]. Single or few layers of Gr can be obtained on the Si face (0001) of hexagonal SiC, either by controlled sublimation of Si at high temperatures (typically > 1650 • C) in Ar at atmospheric pressure or by direct CVD deposition at lower temperatures (~1450 • C) using an external carbon source (such as C 3 H 8 ) with H 2 or H 2 /Ar carrier gases [111].…”
Section: Materials Science Issues and Challengesmentioning
confidence: 99%
“…Up to this moment we considered only the literature reports devoted to propane-argon assisted growth, but there is also some interesting experimental data on CVD growth of graphene by using hydrogen as a carrier gas [114,126,129,131,132,136]. Michon et al [114,126,129] demonstrated the possibility of direct growth of graphene on 6H-SiC (0001) and 3C-SiC/Si substrates. It was concluded that the increase in propane flow in propane-hydrogen gas mixture leads to a significant decrease in the SiC etching rate and increase in graphene thickness.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…The most widely studied among the carbon sources is propane [114,121,124,126,[128][129][130][131][132][133][134][135][136][137]. There is only a few works devoted to ethene [125], toluene [127] and xylene [127] as carbon sources for graphene growth on silicon carbide.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
See 1 more Smart Citation